Wild goose chase : the displacement of influenza research in the fields of poyang lake, China - Fearnley, Lyle (2015)
This article follows transnational avian influenza scientists as they move their experimental systems and research objects into what they refer to as the “epicenter” of flu pandemics, southern China. Based on the hypothesis that contact between wild and domestic bird species could produce new pandemic flu viruses, scientists set up a research program into the wild–domestic interface at China’s Poyang Lake. As influenza comes to be understood in terms of multispecies relations and ecologies in addition to the virus proper, the scientific knowledge of influenza is increasingly dependent on research conducted at particular sites, such as Poyang Lake. What does this movement of influenza research from laboratory to field mean for anthropological concepts of scientific knowledge? A widely shared premise among anthropologists is that scientific knowledge is made in experimental practice, but this practice turn in science studies draws largely from fieldwork inside laboratories. In this article, drawing on fieldwork with both influenza scientists and poultry breeders, I show how scientific research objects can be displaced by the practices of poultry breeders rather than by experimental practice itself. For these poultry breeders, refusing to respect the distinction of wild and domestic, were breeding wild birds.